AGEs, RAGEs and s-RAGE; friend or foe for cancer. (April 2018) - Ahmad, Saheem; Khan, Hamda; Siddiqui, Zeba; Khan, Mohd Yasir; Rehman, Shahnawaz; Shahab, Uzma; Godovikova, Tatyana; Silnikov, Vladimir; Moinuddin,
Abstract: Impaired awareness of glycation biology in cancer initiation and progression is one of the fundamental reasons for its meticulous investigation of the molecules involved in signalling pathway. Glycation of biological macromolecules results in the progression of advanced glycation end-products (AGEs) that proliferates the process of carcinogenesis by activation of transcription factors and release of cytokines. The receptor for advanced glycation end-products (RAGEs) with the binding of its different ligands like; AGEs, HMGB1 and S100 activate the signalling arrays. The activation of downstream signalling pathway ultimately leads to the pathophysiological conditions of diabetes, ageing, neurological disorders and cancers as well as a result of the activation of transcription factors which is discussed in the main body text of this review. However, there might be a likelihood of the positive effect of the HMGB1 and S100 proteins in cancer. Still, some untouched mechanisms might be responsible for the establishment of the function of AGE-RAGE or AGE-sRAGE axis activation that leads to the friend-foe association with the cancers. The levels of RAGE and s-RAGE may be a useful biomarker of ligand-RAGE pathway activation and cancer. Thus, the possibility of providing a potential complement to carcinogenesis is very high which might be an interesting target for therapeutic interventions. This article is an insightful assessment on AGE, RAGE and s-RAGE for its possible role in cancer onset and progression. The novel therapeutic targets for cancer prevention or inhibition are also explained in brief in relation to AGE and RAGE.